2019
DOI: 10.1262/jrd.2018-056
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of spindle assembly checkpoint causes aneuploidy during meiosis II in murine post-ovulatory aged oocytes

Abstract: Mammalian oocyte quality degrades over time after ovulation in vitro, which can cause fatal defects such as chromosomal aneuploidy. As various oocyte manipulations employed in assisted reproductive technology are time consuming, post-ovulatory aging is a serious problem to overcome in reproductive medicine or ova research. In this study, we investigated the effects of postovulatory aging on the incidence of chromosome aneuploidy during meiosis II, with a focus on the expression of functional proteins from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“… 10 , 11 Our previous study showed that post‐ovulatory aging also produces a high frequency of aneuploidy during meiosis II, irrespective of maternal age. 12 The spindle assembly checkpoint (SAC), which functions during cell division, is one of the checkpoint mechanisms that function during the cell cycle. SAC is a monitoring system that equally distributes chromosomes by correctly attaching spindle microtubules to the chromosome kinetochore.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Our previous study showed that post‐ovulatory aging also produces a high frequency of aneuploidy during meiosis II, irrespective of maternal age. 12 The spindle assembly checkpoint (SAC), which functions during cell division, is one of the checkpoint mechanisms that function during the cell cycle. SAC is a monitoring system that equally distributes chromosomes by correctly attaching spindle microtubules to the chromosome kinetochore.…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte maturation depends on the regulation of proteins that determine the correct assembly of meiotic spindles and precise separation of chromosomes. Chromosomal aneuploidy is caused by chromosomal separation errors during meiosis I and II which increases in aged oocytes 37,38 . In our study, three hub genes for ‘oocyte meiosis’ and ‘cell cycle’ SKP1, CCNB1, MAD2L1 were downregulated, but ESPL1 was upregulated.…”
Section: Discussionmentioning
confidence: 55%
“…It can be envisaged that mRNAs (transcripts) of these genes might be translated to maintain the spindle and chromosome morphology and led to delay of the chromosome segregation and subsequent pronuclear formation, as these two MAPK substrates are reportedly implicated in either maintaining the spindle integrity or controlling the microtubule organization of MII mouse oocytes [15]. Similarly, in previous studies it has been reported that post-ovulatory aging of mouse oocytes leads to decreased level of MAD2 (a component of spindle assembly checkpoint) transcripts [74] but increases its (MAD2) protein level [75]. It is likely that the decreased mRNA levels of Sedt2 and Ythdf2 following oocyte vitrification might affect the early embryonic zygote-genome activation process, thus resulting in the lower development of embryos to blastocysts stage, as these two proteins are implicated in either regulation of the trimethylation modification of H3K36 [26][27][28] or degradation of methylated adenine maternal mRNA [24,25].…”
Section: Discussionmentioning
confidence: 80%